Синантропна флора угруповань інтразональної рослинності Північного Причорномор’я - ДУБИНА, ДМИТРО ВАСИЛЬОВИЧ; ДУБИНА, ДМИТРО ВАСИЛЬОВИЧ; ТИМОШЕНКО, ПАВЛО АНДРІЙОВИЧ (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Синантропна флора угруповань інтразональної рослинності Північного Причорномор’я